TRANSFORMASI KELEMBAGAAN GUNA MEMPERKUAT EKONOMI RAKYAT DI PEDESAAN: SUATU KAJIAN ATAS KASUS DI KABUPATEN TABANAN, BALI - SAPTANA -; TRI PRANADJI; SYAHYUTI -; ROOSGANDA ELIZABETH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Weak national economy is resulted from powerless rural economy, and the main cause isfragile supporting institution. If rural economy is not transformed to strong one, the future ofrural economy will be insignificant. There are three pillars in rural community, namely localor traditional communal institution, private sector, and public sector. The research aimed (1)to study characteristics and performance of traditional institution historically, (2) to evaluateprograms related with public economy development in rural areas, (3) to assess the structureof three pillars institution, (4) to find critical points of traditional institutional transform tostrengthen rural economy along with globalization and regional autonomy, and (5) toformulate traditional institution transform model along with globalization and regionalautonomy. The Steps of Rural Economic Institutional Tranformation i.e. : communal societyera, destroyed communal society era, and new communal era. Some Types of InstitutionalTranformation. This research find that the institutional tranformation still in transition stage.There are some type of traditional instiutional transformation, those are: replaced structurewith new structure, adding structure, new missions and objectives, and new norm system.The Mode of Institutional Transformation. As explained in think frame, instituional changeis depend on three of power, i.e. government, market, and community. This research alsofind that community power in market institution have replaced the government support, i.e. incooperatives organization (KUD). Deminishing of the government support gave positiveimpact to KUD, where they are more creative and autonom in planning and action program.Succesfull of development LPD due to the local leadership support and communityparticipation. This is fenomenon where the community principle use in market isntitution,especially in credit program. Institutional transformation mode have five aspects, those areagricultural instituional and organization, leadership, human resources, the value system, andsocio culture.